1954
DOI: 10.1002/j.2050-0416.1954.tb02747.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Free Sugars of the Barley Grain V. Comparison of Sugars and Fructosans With Those of Other Cereals

Abstract: MACLEOD AND PREECEI CEREAL SUGARS AND FRUCTOSANS[J. Inst. Brew.period of time. From this it could be in ferred that 8-resin is not the sole product of changes occurring in a-soft resin; this is what might be expected in view of the known properties of humulone and of the fact that a-soft resin is a mixture. The results of the present experiments do not, in fact, permit the reaching of any definite conclusions concerning the genesis of 8-resin for, as yet, there is no information concerning the storage changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

1955
1955
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 7 publications
0
9
2
Order By: Relevance
“…Early work by other authors also suggested that fructans together with sucrose and raffinose are being used as substrate during respiration in the initial stages of germination before hydrolysis of starch begins (MacLeod et al 1953;MacLeod and Preece 1954). This idea is supported by the findings of other authors (Harris and MacWilliam 1954).…”
Section: Grain and Malt Samplesmentioning
confidence: 59%
See 1 more Smart Citation
“…Early work by other authors also suggested that fructans together with sucrose and raffinose are being used as substrate during respiration in the initial stages of germination before hydrolysis of starch begins (MacLeod et al 1953;MacLeod and Preece 1954). This idea is supported by the findings of other authors (Harris and MacWilliam 1954).…”
Section: Grain and Malt Samplesmentioning
confidence: 59%
“…Some authors suggested that if this is the case, genotypes/varieties with high fructan and glucose concentrations may germinate more efficiently and thus malt more readily (Harris and MacWilliam 1954;Smith and Morgan 1980). These studies have shown that there is considerable variation in the acid soluble β-glucan, fructans and free sugar content of some barley varieties (MacLeod et al 1953;MacLeod and Preece 1954;Smith and Morgan 1980;Cozzolino et al 2014a, b Fructans content (% w/w) Apparent aƩenuaƟon limit (%) R 2 = 0.03 RMSE = 3.42 …”
Section: Grain and Malt Samplesmentioning
confidence: 95%
“…These results provide evidence for enhanced con centrations of fructosan in better malting varieties. The role of fructosan in barley is not clear;10 detailed studies of isolated cell walls have been made on material inactivated with 80 per cent ethanol18 which dissolves fructosans of intermediate complexity, [14][15][16][17][18] and results in preparations free from fructose. 13 However, although fructosans of high molecular weight do occur in barley," it is more likely that fructosans have a metabolic rather than structural significance; MacLeod et al suggest" that fructosans, together with sucrose and raffinose, fuel respiration in the initial stages of germination before hydrolysis of starch begins.…”
Section: Discussionmentioning
confidence: 99%
“…When the yield of polysaccharide was sufficiently large, fractionation by means of ammonium sulphate was carried out. In the hands of Preece and Mackenzie (1952) this technique has proved outstandingly useful for separating pure ^-glucosan from crude water-soluble polysaccharides of barley and oats, and, since a survey of cereal grains (MacLeod and Preece, 1954) had shown a remarkable variation in the content of this particular carbohydrate, it was felt that the presence or absence of this p-glucosan might prove a point of some significance.…”
Section: Water-soluble Polysaccltaridesmentioning
confidence: 99%
“…However, a general survey of the water-soluble carbohydrates of common cereal grains (MacLeod and Preece, 1954) has shown that considerable differences are possible both in the relative quantities present and in the chemical constitution of certain carbohydrate fractions. It seemed of interest, therefore, to extend this work from the cereals to include a representative series of seeds of wild grasses, so as to establish the range of composition possible within a complete natural family; even if the results of such a survey shed no light on taxonomic problems, they should be at least of some general biochemical interest.…”
Section: Introductionmentioning
confidence: 99%